Homoleptic d10 metal complexes containing ferrocenyl functionalized dithiocarbamates as sensitizers for TiO2 based dye-sensitized solar cells. (December 2018) - Neetu,; Manar, Krishna Kumar; Srivastava, Pankaj; Singh, Nanhai
Graphical abstract: Highlights: New d 10 metal complexes studied for sensitization activities in TiO2 based DSSC. High efficiency (6.2%) of Zn-1 based cell, close to that obtained with N719 (6.9%). Zn-1 demonstrated better output due to structural features, greater dye coverage and longer electron life time. Abstract: Four synthesized d 10 metal complexes, namely, ferrocenyl based pyridyl functionalized dithiocarbamates macro-cyclic metal-organic coordination polymers, [M(L)2 ]∞ (M = Zn(II), L = (N-ferrocenyl-methyl-N-pyridin-4-ylmethyl)dithiocarbamate Zn-2 ; Cd (II), L = (N-ferrocenyl-methyl-N-pyridin-3-ylmethyl) dithiocarbamate Cd-3 and dimers [M(L)2 ]2 (M = Zn(II), Hg(II), L = (N-ferrocenyl-methyl-N-pyridin-3-ylmethyl) dithiocarbamate, Zn-1 and Hg-4 were studied for their sensitization activities when anchored on TiO2 thin film electrode and employed as photoanode in dye-sensitized solar cells (DSSC). The absorption spectra of test dyes in dichloromethane solution indicated absorption in 400–500 nm range for all complexes, revealing the possibility of their use as photosensitizers for TiO2 . The cyclic voltammetry (CV) demonstrated quasi-reversible behavior for all the complexes. All the dye sensitizers showed significant light harvesting properties with an exceptionally high light-to-electrical energy conversion efficiency (6.23%) shown by Zn-1 complex which was close to that obtained with standard Ru dye, N719 (6.96%) under similar experimental conditions. The better performance of Zn-1 complex compared to other studied dye sensitizers were attributed to its structural features. The extent of interfacial charge recombination and electron lifetime were evaluated by the electrochemical impedance spectroscopy (EIS).